ATTITUDES OF PARENTS AND TEACHERS TOWARDS MATHEMATICS EDUCATION IN THE CONTEXT OF STEAM EDUCATION - Rutkiene, Ausra; Narusaitiene, Ginta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The pre-school period is valuable in itself. It is at this age that the child's most important personality traits, his or her perception, thinking, communication, etc., develop. STEAM goes hand in hand with the development of 21st century skills and should be included as early as possible in the curriculum. Children's early experiences with science, technology, engineering and mathematics and the arts influence their future success in these areas. When teachers give children early opportunities to learn maths and science in an interactive environment that builds communication and collaboration skills, children are more confident and competent in these subjects. This not only makes higher education more accessible to children but also contributes to a well-prepared society. Survey of 116 teachers and 104 parents identified that parents of pre-school children are more accurate in identifying the disciplines that STEAM education integrates, they perceive that the teacher's background in mathematics and science influences children's mathematical and science education, and that young children can apply early mathematical concepts. Parents identified advantages and barriers to the successful implementation of STEAM in pre-school education.